FIRM VALUE IN IDX: EFFECT OF GREEN BANKING DISCLOSURE, EARNING QUALITY AND INTELLECTUAL CAPITAL - Hasatiru Auwa; Ghazali Syamni; Darmawati Muchtar; Muttaqien (Journal of Accounting Research, Utility Finance and Digital Assets, 2024)
This research aims to empirically test the influence of green banking, profit quality and intellectual capital on banking firm value as proxied by Price to Book Value (PBV) in banks listed on the Indonesia Stock Exchange during the 2018-2022 period. The data in this research was accessed on the official website www.idx.co.id. The sample used in this research was 42 companies. The data analysis method in this research uses the panel data regression analysis method with the Stata 17 application tool. The research results found that green banking has a negative and significant effect on firm value. This is because investors have not responded well to green banking, besides that the costs for implementing green banking are quite large so companies have not been able to optimize it. Meanwhile, the quality of profits and intellectual capital have no effect on firm value. This is because the quality of profits and intellectual capital has not been responded well by investors. Firm value can explain the firm's future prospects and can be used to assess it as a whole. Investors can make decisions about investing by looking at the firm's share price and the amount of assets produced by the firm.